Investigation of photoinduced orientation ordering in polymethacrylates with side-chain azobenzene moieties - Nadtoka, Oksana; Yaroshchuk, Oleg (Publishing House of Lviv Polytechnic National University, 2012)
The initial and the photoinduced 3D orientational order in the films of two methacrylic polymers containing azobenzene groups with electron-donor or electron-acceptor substituents was studied by using null ellipsometry and UV/Vis absorption spectroscopy. The 3D order was induced by monochromatic polarized light of two different wavelengths corresponding to ππ* and nπ* absorption bands of azochromophores. We found that, depending on the excitation wavelength and terminal substituents of azochromophores, recording kinetics of photoinduced anisotropy in the polymers is dominated by either angular redistribution or angularly selective trans-cis isomerization of the chromophores originally being mainly in the trans-form. Before irradiation, the azobenzene groups in the films of all polymers show preference to the out-ofplane ordering. Scenario of the order transformation under irradiation depends on the prevailing mechanism of the photoinduced anisotropy. In case of angular redistribution,initial positive uniaxial order of azochromophores is transformed into the negative uniaxial order characterized by random orientation of these units in the plane perpendicular to the polarization direction of the exciting light. In turn, in case of photoselection, the chromophores approach a zero-order (spatially isotropic) state due to exhaustion of the anisotropic trans-isomers in all directions. The transient orientational structures in these kinetic processes are biaxial. Вивчено кінетику фотоіндукованого впорядкування двох метакрилових полімерів, що містять азобензольні групи з електрон-донорними або електрон-акцепторними замісниками, при їх опроміненні за різних довжин хвиль. Експериментальні дослідження було проведено з використанням методів нуль-еліпсометрії та спектроскопії. Показано, що азофрагменти орієнтуються в залежності від довжини хвилі за механізмом фотоорієнтації або фотоселекції. За механізмом фотоорієнтації азохромофори спонтанно розміщуються в площині, перпендикулярній вектору поляризації світла Eex. У випадку, коли переважає механізм фотоселекції, 3-мірний розподіл азохромофорів у стані насичення є ізотропним завдяки суттєвому вичерпанню анізотропних транс-ізомерів.
Дослідження фотоіндукованої орієнтації в поліметакрилатах з бічними азобензольними фрагментами
Keywords: azopolymer; polymethacrylate; photoinduced orientation; азополімер; поліметакрилат; фотоіндукована орієнтація